ANALISIS NILAI RELIGIUS DALAM SYAIR NASYID SALSABIL - Eliana Eliana; Razali Razali; Siti Sarah Fitriani (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2020)
The objectives of this study were (1) to describe the religious values contained in the verse Nasyid Salsabil, (2) to describe the way the poets describe the religious values in the verse nasyid Salsabil. The method used is a qualitative research method. The type of approach in this research is content analysis. The data in this study were all parts of the nasyid lyrics which contained religious values, with the source of the data being the verse nasyid Salsabil. Based on the results of the analysis, the data depicted in Salsabil's verse are (1) the relationship between man and God, including; pious and pray, (2) human relations with other humans, including; please help, advice, and affection, (3) human relations with society including; harmony, and wisdom, (4) human relations with oneself including; be humble and maintain self-respect. The results showed that the relationship between humans and God which is described in the verse of Nasyid Salsabil is that people repent and prostrate to Allah and read the words of Allah. Pray by asking Allah to be cleansed of his heart, asking Allah for his life to be preserved, and asking Allah for the blessing given to his mother. The relationship between humans and other humans as described in the verse of Nasyid Salsabil, namely unifying hearts to fight for religion, advising others to be enthusiastic in fighting for religion, directed to their children to always know God, remind others of avoiding acts that are prohibited by religion, advising to provide maternal services, advising married women and advice to remember death and. A mother's love for her child and a mother's patience in conceiving. The relationship between humans and society as described in nasyid verseis unity in upholding religion and maintaining Islamic identity and greeting and respecting invited guests. The relationship between man and himself which is depicted in nasyid verse is to greet and apologize, and to maintain Islamic brotherhood.